2014
DOI: 10.1177/003335491412900409
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Crashes from Drivers Testing Positive for Drugs in the U.S., 1993–2010

Abstract: The profile of a drugged driver has changed substantially over time. An increasing share of these drivers is now testing positive for prescription drugs, cannabis, and multiple drugs. These findings have implications for developing interventions to address the changing nature of drug use among drivers in the U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Δ 9 -THC has been shown to impair cognition, psychomotor function, and actual driving performance in a dose related manner. The degrees of impairment observed in laboratory or actual driving tests after doses up to 300 µg/kg Δ 9 -THC were comparable to the impairing effects of an alcohol dose producing a blood alcohol concentration ≥ 0,05g/dl [10][11][12]. Data on THC used as medical prescriptions are limited; only Stott et al described the single and multiple dose pharmacokinetics of THC/CBD oromucosal spray treatments on twelve subjects, whose received either single doses of THC/CBD spray as multiple sprays (from 5.4 mg THC and 5.0 mg CBD to 21.6 mg THC and 20.0 mg CBD).…”
Section: Introductionmentioning
confidence: 74%
“…Δ 9 -THC has been shown to impair cognition, psychomotor function, and actual driving performance in a dose related manner. The degrees of impairment observed in laboratory or actual driving tests after doses up to 300 µg/kg Δ 9 -THC were comparable to the impairing effects of an alcohol dose producing a blood alcohol concentration ≥ 0,05g/dl [10][11][12]. Data on THC used as medical prescriptions are limited; only Stott et al described the single and multiple dose pharmacokinetics of THC/CBD oromucosal spray treatments on twelve subjects, whose received either single doses of THC/CBD spray as multiple sprays (from 5.4 mg THC and 5.0 mg CBD to 21.6 mg THC and 20.0 mg CBD).…”
Section: Introductionmentioning
confidence: 74%
“…Psychoactive prescription drugs are commonly and increasingly identified in the blood and urine samples of drug-impaired drivers (Bezemer et al, 2014;Burch et al, 2013;Christophersen and Mørland, 2008;Jones et al, 2009;Karjalainen et al, 2015;NBFM, 2014;Wilson et al, 2014). Because psychoactive drugs may impair driving ability, their users are at increased risk of traffic accidents (Dassanayake et al, 2011;Gustavsen et al, 2008;Hetland and Carr, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al ([2014]) found that 54.9% of marijuana-positive drivers in the United States had elevated BACs. Various studies have demonstrated that the combined use of marijuana and alcohol is associated with significantly greater cognitive impairment and crash risk than the use of one alone (Asbridge [2014]; Downey et al [2013]; Ramaekers et al [2004]; Sewell et al [2009]).…”
Section: Reviewmentioning
confidence: 99%